And I found between them, and I found, and I found between them Clinics in birds (Journal of the College of Basic Education, 2022)
The task that the critic carries out requires a reader who is aware of what he is saying in order to be able to beThe complementary cycle of the equation: the reader - the reader - the critic. A critic without a reader is not a critic just as a reader without a critic does not exist at all.From theories of reception and reader response criticism. This theoretical proposition finds its field applied in various monetary productions that vary in function.which it achieves in relation to the read, which revolves around literary, poetic and narrative productions, as the style of